2017
DOI: 10.5124/jkma.2017.60.7.588
|View full text |Cite
|
Sign up to set email alerts
|

Infant, maternal, and perinatal mortality statistics in the Republic of Korea, 2014

Abstract: descriptive presentation and analysis of the national data. The number of infant deaths was 1,305 out of 435,435 live births in 2014, and the infant mortality rate was 3.0. The number of maternal deaths was 48. The maternal mortality ratio per 100,000 live births was 11.0. The maternal mortality ratio per 100,000 women of child-bearing age (15 to 49 years old) was 0.37. The number of perinatal deaths was 1,365, and the perinatal mortality rate was 3.1. The number of fetal deaths was 5,317. The fetal mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Through various efforts, including improvements in prenatal and neonatal care, Korea has decreased the infant mortality rate from 4.7 in 2004 to 3.0 in 2014 39 . Moreover, our study revealed a continued decline in the incidence of CP in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Through various efforts, including improvements in prenatal and neonatal care, Korea has decreased the infant mortality rate from 4.7 in 2004 to 3.0 in 2014 39 . Moreover, our study revealed a continued decline in the incidence of CP in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…First, the underlying causes of death specified in the death certificates according to the ICD by the World Health Organization were determined. The causes of death were also determined in accordance with the Korean standard classification of disease and case of death [13,14]. To analyze the trends in the cause of death, we divided the study period into the following intervals; 2006-2010, 2011-2014, and 2015-2018.…”
Section: Confirmation Of Diabetes and Death Certificatesmentioning
confidence: 99%